2009
DOI: 10.1177/1096348009349821
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy of Academic Quality Indicators for U.S.-Based 4-Year Undergraduate Hospitality Management Programs

Abstract: The purpose of the study was to classify quality indicators into unique construct groups. Seventy-two quality indicators were investigated as predictors of undergraduate hospitality management program excellence. A multidimensional approach was used on a sample of 277 stakeholders to answer relevant research questions. By cluster analysis of primary quality indicators for undergraduate hospitality management programs, three construct groups were identified: (a) students/alumni, industry support, faculty; (b) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 19 publications
(26 reference statements)
0
19
0
Order By: Relevance
“…All three levels must be acknowledged and addressed accordingly to ensure that an appropriate curriculum is developed and resources are utilized effectively. Assante, Huffman, and Harp (2010) posited that program quality indicators are most frequently found in three broad areas: (1) students and alumni, industry support, and faculty; (2) facilities and curriculum; and (3) research. They suggested that these indicators could be used for program evaluation, planning, and development.…”
Section: Industry Involvement In Curriculum Developmentmentioning
confidence: 99%
“…All three levels must be acknowledged and addressed accordingly to ensure that an appropriate curriculum is developed and resources are utilized effectively. Assante, Huffman, and Harp (2010) posited that program quality indicators are most frequently found in three broad areas: (1) students and alumni, industry support, and faculty; (2) facilities and curriculum; and (3) research. They suggested that these indicators could be used for program evaluation, planning, and development.…”
Section: Industry Involvement In Curriculum Developmentmentioning
confidence: 99%
“…In the classroom environment, students think industrybased experiential learning assignment is more suitable for learning practical knowledge and organizational function, and establishing realistic career expectations and professional networks of contact. Not only in student learning, but also in determining the quality of undergraduate hospitality management programs, provision of student internships plays an important role (Assante et al, 2010).…”
Section: The Impact Of Information Source On Information Searchmentioning
confidence: 99%
“…Despite the importance of internship in tourism and hospitality education learning (Assante, Huffman, & Harp, 2010;Gruman, Barrows, & Reavley, 2009; B. P. Kim, McCleary, & Kaufman, 2010), there is surprisingly little academic research that studies how students conduct internship information search. Existing studies have mainly examined internship experience (Beggs, Ross, & Goodwin, 2008;Cho, 2006;Lam & Ching, 2007;Solnet, Kralj, Kay, & DeVeau, 2009), career decision making (B. P. Kim et al, 2010;Ko, 2007), and experiential learning (Gruman et al, 2009;S.…”
Section: Introductionmentioning
confidence: 99%
“…Goodman and Sprague (1991) argued that there is an urgent need to reposition hospitality programs and to adapt to industry changes, lest these programs face the fate of other specialized programs, such as insurance or banking, which have been absorbed into general business management programs. Assante, Huffman, and Harp (2010) also argued that hospitality programs must constantly evolve to satisfy the roles of training and providing the industry's future leaders. The goal of hospitality programs is to maintain the high quality of graduates and ensure their placement and retention within the hospitality industry (Nelson & Dopson, 2001).…”
Section: Introductionmentioning
confidence: 98%